1999
DOI: 10.2307/2656925
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic dioecy and leaky dioecy in endemic species of Dombeya (Sterculiaceae) on La Re´union

Abstract: The high frequency of dioecy on oceanic islands such as Hawaii and New Zealand has attracted a great deal of attention from plant evolutionary biologists. One reason suggested for the high prevalence of dioecy on oceanic islands is that taxa considered truly dioecious may have occasional hermaphrodite flowers, i.e., show leaky dioecy. In this study, we quantified the presence and distribution of leaky dioecy in a group of congeneric endemic species of the genus Dombeya (Sterculiaceae) on La Réunion island (Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 39 publications
4
43
0
1
Order By: Relevance
“…Dombeya formosa shows also flower size dimorphism between sexes (i.e. male flowers tend to be bigger than female flowers except for the gynoecium), a feature also found in the other endemic species of Dombeya on La Réunion (Humeau et al 1999a). The distinctions in both floral and vegetative features are emphasized by the striking disjunction of the flowering periods, i.e.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Dombeya formosa shows also flower size dimorphism between sexes (i.e. male flowers tend to be bigger than female flowers except for the gynoecium), a feature also found in the other endemic species of Dombeya on La Réunion (Humeau et al 1999a). The distinctions in both floral and vegetative features are emphasized by the striking disjunction of the flowering periods, i.e.…”
Section: Discussionmentioning
confidence: 77%
“…While the flowers of a male specimen present a reduced gynoecium without stigma and ovule, female flowers of Dombeya formosa show smaller staminodes and stamens and do not produce viable pollen (Figs. 1;2G, H;Humeau et al 1999a). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations utilizing populations of nursery grown plants have revealed that Kadua haupuensis is subdioecious or "leaky dioecious," sensu Humeau et al (1999). That is, these taxa are not truly dioecious as they may produce occasional hermaphroditic flowers or individuals.…”
Section: Kadua Haupuensismentioning
confidence: 99%
“…The presence of occasional opposite sex or hermaphrodite flowers on the same individual of a dioecious species is referred as leaky dioecy. Several cases of leaky dioecy have been reported on oceanic islands, the most well-known examples being, Coprosma in the Juan Fernandez Islands, Sanctambrosia in the Desventuras Islands (see Baker and Cox 1984), Fragaria, Plantago in Hawaii (Carlquist 1974) Cotula, Clematis, Pittosporum, Dodonea, Alectryon, Anisotome, Astelia in New Zealand (Godley 1979) and Dombeya in Reunion Island (Humeau et al 1999) situated in the Indian Ocean, 150 km to the South West of Mauritius. These two islands are volcanic and form part of the Mascarene archipelago.…”
Section: Introductionmentioning
confidence: 99%